2018
DOI: 10.1007/s00192-018-3697-0
|View full text |Cite
|
Sign up to set email alerts
|

What are the concerns and goals of women attending a urogynaecology clinic? Content analysis of free-text data from an electronic pelvic floor assessment questionnaire (ePAQ-PF)

Abstract: Free-text reporting in ePAQ-PF is utilised by patients and facilitates self-expression and discussion of issues impacting on HRQOL. The significant relationship between recorded free-text concerns and ePAQ-PF domain scores suggests convergent validity for the instrument. Development and psychometric testing of a domain to assess body image is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…This follows, as scarring would be most relevant to patients following surgical intervention or perineal trauma, whereas ePAQ-PF is mostly completed by new referrals to clinic. Previous content analysis of ePAQ-PF free-text responses reports that 16.3% were concerned about smell and only 6.9% about scarring [14]. Comparing these figures to our results (Table 1) suggests that inclusion of these body-image items has increased symptom disclosure, highlighting the value of questionnaire interviewing in this context.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…This follows, as scarring would be most relevant to patients following surgical intervention or perineal trauma, whereas ePAQ-PF is mostly completed by new referrals to clinic. Previous content analysis of ePAQ-PF free-text responses reports that 16.3% were concerned about smell and only 6.9% about scarring [14]. Comparing these figures to our results (Table 1) suggests that inclusion of these body-image items has increased symptom disclosure, highlighting the value of questionnaire interviewing in this context.…”
Section: Discussionsupporting
confidence: 71%
“…A previous content analysis study of responses to the free-text item in ePAQ-PF, which asks patients 'Considering the issues that currently concern you the most, what do you hope to achieve from any help, advice or treatment? ', assessed responses from almost two thousand urogynaecology clinic patients and found that 11% of patients reported bodyimage concerns via the free text item [14]. Body image is not currently assessed by ePAQ-PF in any of its 19 symptom domain areas which use multiple choice questions assessing frequency and impact of symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…Women with pelvic floor disorders were also more likely to seek care when the adverse impact on the quality of life was greater [2]. Concerns of affected women varied from worrying about body image like appearance and smell to improving sexual function, reducing pad use and becoming more physically active [6]. Research on patients goal achievement of treatment highlighted that many women preferred to be dry but would not mind if the incontinence only improves to be able to manage their daily activities [6].…”
mentioning
confidence: 99%
“…Concerns of affected women varied from worrying about body image like appearance and smell to improving sexual function, reducing pad use and becoming more physically active [6]. Research on patients goal achievement of treatment highlighted that many women preferred to be dry but would not mind if the incontinence only improves to be able to manage their daily activities [6]. Interestingly, those studies described similar patient concerns and goals despite being reported from different countries.…”
mentioning
confidence: 99%
See 1 more Smart Citation